The Student’s Olympiad as a Form of Professional Training for Analysts-Statistician - Honchar, I. A.; Zaiets, S. V. (Statistics of Ukraine, 2019)
The article describes the practical experience in organizing the first All-Ukrainian Olympiad on Economic Analytics and Statistics, aiming to improve the quality of professional training, increase the students’ interest to in their chosen profession and create conditions for students to acquire the necessary professional skills and abilities, and gain experience in educational and professional activities. The assessment of the foreign labor market for specialists in Statistics / Analytics / Finance, allowing to determine the relevance of the profession in the near future, is given. A review of the competencies of a statistics analyst, acquired by future specialists in domestic higher education institutions, is made. It is emphasized that formation of the professional competencies cannot be confined to individual disciplines or educational programs; it requires the conditions for the effective influence of educational technologies, methods, organizational forms, learning environments, including the participation of students in intellectual competitions and Olympiads. For understanding the structure and specificity of tasks at the first All-Ukrainian Olympiad on Economic Analytics and Statistics, examples of the tasks simulating various aspects and components of an analytical study are given. The results shown by the students participating in the Olympiad are analyzed in comparison with the current requirements to the professional competencies in analytics and statistics. The conclusion about the diagnostic function of Olympiad is made. The link to the web-site where the Olympiad materials are displayed, allows for using the innovative approaches to lecturing in higher educational institutions as part of the academic program for economic analysts. The current trends in support of gifted students are outlined, and proposals are made on how to improve the effectiveness of student Olympiads in Economic Analytics and Statistics. Measures for the potential implementation of “social lift” system for young statistics analysts are highlighted. It is stressed that the training of students for Olympiads can be a means elevating their professional and intellectual level, motivating their self-organization and self-realization, and increasing their overall statistical education. Further research will focus on feasibility studies and proposals related with adoption of new professions dealing with statistical analytics.